Impacto de la proliferación de construcción de viviendas rurales de propietarios en comunidad por venta de porcentajes legalizados en notaria, en Restrepo Meta (2019)
In the present monograph there is realized an analysis of the current situation of Restrepo Meta's municipality, with what it concerns to the impact that generates the construction of owners' rural housing in community and in the specific case of construction without license, having as principal information to value these problematics the juridical normativity. This investigation proves being important, since it allows to determine accurately since they present diverse general and particular interests in the construction of rural housing in the municipality of the Restrepo in the Meta, and as this ecology is reflected in the territory and his structure, being important to establish the elements in which it is allowed formulate possible solutions and especially direct persons in charge on whom there would relapse the duty to solve the situations that stem in the municipality.